Anti-fungal secondary metabolites and hydrolytic enzymes from rhizospheric bacteria in crop protection: a review (Journal of Bangladesh Academy of Sciences, 2021)
Plant growth promoting rhizobacteria (PGPR) residing in soil rhizosphere provide enormous beneficial effects to a plant host producing diverse secondary metabolites and enzymes useful for plant growth and protection. Siderophores, antibiotics, volatile compounds and hydrolytic enzymes are the major molecules secreted by the PGPRs, which have substantial antifungal properties and can provide plant protection. These compounds are responsible for the lysis and hyperparasitism of antagonists against deleterious fungal pathogens. Siderophore-producing PGPRs function by depriving the pathogen of iron nutrition. Antibiotics have been reported to be involved in the suppression of different fungal pathogens by inducing fungistasis, inhibition of spore germination, lysis of fungal mycelia. The PGPRs also secrete a wide range of low molecular weight volatile organic compounds (VOCs) that inhibit mycelial growth, sporulation, germination of phytophathogenic fungi, etc. Hydrolytic enzymes, mostly chitinase, protease and cellulose, lyse the cell wall of fungi. Therefore, plant growth-promoting rhizobacteria can be considered as an effective, eco-friendly, and sustainable replacement to the chemical fungicides. There are many PGPRs that perform very well in controlled conditions but not in field conditions, and hence the commercializing of hese products is not easy.  Development of formulations with increased shelf life, a broad spectrum of action and consistent performance under field conditions can pave the way for commercializing the PGPRs at a faster rate.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, 69-84, 2020